PENGEMBANGAN LKPD BERBASIS GEOGEBRA DAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS VII SMPN 17 KOTA BENGKULU - Nesta, Ridho Agio; Susanta, Agus; Haji, Saleh (LPPM Universitas Bina Bangsa, 2024)
This study aims to produce GeoGebra-based and Problem-Based Learning (PBL) worksheets (LKPD) that are valid, practical, and effective in improving the understanding of mathematical concepts among seventh-grade students at SMPN 17 Kota Bengkulu. The research employs development studies methods with preliminary and prototyping phases through formative evaluation, including self-evaluation, one-on-one, expert review, small group, and field tests. The results indicate that the LKPD is deemed valid based on expert reviews and one-on-one evaluations after revisions in content, construction, and language. The LKPD is also practical and easy for students to use, as evidenced by small group trials and student feedback. The effectiveness of the LKPD is demonstrated by an increase in the average mathematics scores and classical learning completeness, with 89.28% of students achieving scores above the minimum mastery criterion (KKM) ≥ 75. This indicates that the GeoGebra-based and PBL LKPD is effective in enhancing students' understanding of mathematical concepts